EVESOR, a model-based, multiparameter, Phase I trial to optimize the benefit/toxicity ratio of everolimus and sorafenib. (April 2017) - El-Madani, Mévidette; Colomban, Olivier; Tod, Michel; Maillet, Denis; Peron, Julien; Rodriguez-Lafrasse, Claire; Badary, Osama A; Valette, Pierre-Jean; Lefort, Thibaud; Cassier, Philippe; El-Shenawy, Siham M; EL-Demerdash, Ebtehal; et al.
Aim: This novel multiparameter Phase I study aimed to optimize doses/dosing schedules of everolimus and sorafenib drug combination, based on modeling/simulation (NCT01932177).Patients & methods: About 26 patients with solid tumors were treated in four different dosing schedules. Everolimus once daily + sorafenib twice daily were given continuously in arms A and B, and intermittently in arms C (alternating every other week) and D (everolimus continuous and sorafenib 3 days on/4 days off).Results: Continuous schedules exhibited higher toxicity risks than intermittent schedules (64.1 vs 35.9%; p < 0.0001), and trends for lower disease control rates (80 vs 100%). No significant pharmacokinetic interaction was identified.Conclusion: Feasibility of EVESOR trial is demonstrated. Intermittent schedules might provide better tolerance and efficacy than continuous schedules.